A hybrid system using a regenerative electrochemical cycle to harvest waste heat from the proton exchange membrane fuel cell. (15th December 2015) - Long, Rui; Li, Baode; Liu, Zhichun; Liu, Wei
Abstract: A new hybrid system consisting of a PEMFC (proton exchange membrane fuel cell) subsystem and a TREC (thermally regenerative electrochemical cycle) subsystem is proposed to convert the waste heat produced by the PEMFC system into electricity. The performance of the hybrid system and its corresponding subsystems is analyzed. Results reveal that there exists optimal current densities of the PEMFC and TREC systems leading to the maximum power output of the hybrid system. With the maximum power output as the objective function, an optimization of the hybrid system based on genetic algorithm method is conducted under different operating temperatures of the PEMFC subsystem. The power output of the hybrid system is 6.85%–20.59% larger than that of the PEMFC subsystem. And the total electrical efficiency is improved by 2.74%–8.27%. The corresponding electrical efficiency of the TREC is 4.56%–13.81%. The hybrid system proposed in this paper could contribute to utilizing the fuel energy more efficiently and sufficiently. Highlights: A hybrid power system consisting of a PEMFC and a TREC subsystems is proposed. Parameters' impacts on performance of the hybrid system have been analyzed. The maximum power output of the hybrid system is investigated based on genetic algorithm. Total power output of the hybrid system is 7.63%–18.84% larger than that of the PEMFC subsystem.